Income taxation : principles and laws with accounting applications - Valencia, Edwin G.; Roxas, Gregorio F. (Baguio City : Valencia Educational Supply, 2013)
This book is designed as a textbook in the course Income Taxation covering comprehensive topics included in the CPA and Bar Examinations.
Chapter 1 : General Principles and Concepts of Taxation 1 -- Chapter 2 : Tax Administration 69 -- Chapter 3 : Concept of Income 141 -- Chapter 4 : Gross Income 189<Chapter 5 : Exclusion from Gross Income 259 -- Chapter 6 : Fringe Benefit Tax 309 -- Chapter 7 : Review Questions and Problems 393 -- Chapter 8 : Deductions from Groos Income 419 -- Chapter 9 : Losses 497 -- Chapter 10 : Basic Income Tax Patterns 527 -- Chapter 11: Income Tax Individuals 545 -- Chapter 12 : Income Tax of Corporations 601 -- Chapter 13 : Income Taxes of Partnerships, Co-Ownerships, Joint Ventures 655 -- Chapter 14 : Income Taxes of Estates and Trusts 683 -- Chapter 15 : Withholding Taxes 705 -- Annex A 722 -- Annex B 723 -- Annex C 724
Keywords: INCOME TAX -- LAW AND LEGISLATION -- PHILIPPINES